Social participation in Protected Areas: the case of the Ilha do Cardoso State Park (Sao Paulo, Brazil) - Risso, Luciene Cristina [UNESP] (Univ Fed Goias, Inst Estudos Socio-ambientais, 2016)
The social participation in protected areas of Brazil is guaranteed by the Law 9985/2000, which created the National System of Conservation Units. Thereby, to evaluate the social participation and the vision of the community representatives concerning the advisory board of the Ilha do Cardoso State Park (south coast of Sao Paulo, Brazil) was constituted the central objectives of this work. In order to investigate this question, the methodology consisted of a literature search on the theme and the park studied; application of two semi-structured questionnaires, organization and reflection of this database, and finally, some propositions. As the results obtained from questionnaire applied to the community representatives of the advisory board from the park, these recognized the importance and effectiveness of participative instance, mainly the matter of being heard and about the regulation of land use. In this way, the boards are odd instruments in the management, substantially because they attenuate the complex problematic between parks and communities.
Keywords: protected areas; conflicts; traditional communities; participative management